Towards Comparative and Aggregate Vulnerability: An Analysis of Welfare Distributions in Rural Provinces in Thailand and Vietnam - Bernd Hardeweg; Andreas Wagener; Hermann Waibel (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Several measures of vulnerability to poverty have been suggested in the literature. In practise, only little is known about the robustness of vulnerability comparisons based on these often quite specific measures. The theory of stochastic orders can be applied to shed some light on such issues. In the DFG research project "Impact of Shocks on the Vulnerability to Poverty: Consequences for Development of Emerging Southeast Asian Economies" (DFG FOR 756), an extensive panel survey was carried out in six rural provinces of Thailand and Vietnam in 2007. We establish cumulative distribution functions for income and consumption at the provincial level and search for stochastic dominance relations between these distributions. Our comparisons allow for initial, but quite robust conclusions on welfare and provide benchmarks for assessing the vulnerability to poverty in the research regions.
Keywords: D31; I32; O15; 330; welfare distribution; stochastic ordering; vulnerability